2017
DOI: 10.1016/j.ophtha.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Management of Infectious Keratitis

Abstract: Infectious keratitis is a major global cause of visual impairment and blindness, often affecting marginalized populations. Proper diagnosis of the causative organism is critical, and while culture remains the prevailing diagnostic tool, newer techniques such as in vivo confocal microscopy are helpful for diagnosing fungal keratitis and Acanthameoba. Next generation sequencing holds the potential for early and accurate diagnosis even for organisms that are difficult to culture by conventional methods. Topical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
327
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(391 citation statements)
references
References 123 publications
2
327
0
11
Order By: Relevance
“…However, there have been several reports of ACV R strains causing HSK in immunocompetent patients . Thus, considering the rise of the resistant viruses against the current antivirals and the adverse effect of corticoids, there is a need to search for new potential anti‐HSV agents that act with different mechanisms. In this sense, the finding of novel compounds that inhibit both viral multiplication and the immunopathology triggered by the virus is an interesting approach that is being considered …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been several reports of ACV R strains causing HSK in immunocompetent patients . Thus, considering the rise of the resistant viruses against the current antivirals and the adverse effect of corticoids, there is a need to search for new potential anti‐HSV agents that act with different mechanisms. In this sense, the finding of novel compounds that inhibit both viral multiplication and the immunopathology triggered by the virus is an interesting approach that is being considered …”
Section: Introductionmentioning
confidence: 99%
“…[6] However, corticosteroids have adverse side effects, and there is concern that they prolong viral shedding. [6] In most HSVrelated diseases, the prevalence rates of acyclovir (ACV) resistance are much higher among immunocompromised patients. However, there have been several reports of ACV R strains causing HSK in immunocompetent patients.…”
Section: Introductionmentioning
confidence: 99%
“…Topical antibiotics remain the best treatment for bacterial keratitis. It was found that all frequently used antibiotics are equally effective, but the final outcome is not satisfactory because of corneal melting, scaring and perforation [29]. Treatment used varies depending on geographical location and available local antimicrobial susceptibility of Pseudomonas isolates.…”
Section: Management Of P Aeruginosa Keratitismentioning
confidence: 99%
“…Meropenem and ciprofloxacin with 90% of isolates showed synergistic or additive effect. This made combined anti-microbial a potential treatment against multi drug resistant strains [29]. Most common prescribed drugs are ciprofloxacin and tobramycin, a fortified aminoglycosides.…”
Section: Management Of P Aeruginosa Keratitismentioning
confidence: 99%
“…associated with chronic and recurrent ocular disease, characterized by conjunctivitis, corneal ulceration, and epithelial and stromal keratitis, often leading to corneal scarring and loss of transparency (3). All currently approved therapies for ophthalmologic alphaherpesvirus infection rely on nucleoside analogues that prevent base pairing when incorporated into the growing DNA polymer, thus inhibiting genome replication (4). However, and despite the proven value of these drugs in limiting HHV-1-associated corneal damage, effective treatment of this condition remains challenging due to toxicity concerns, the frequency of treatment required, and the potential for selection of drug-resistant variants, especially in immunocompromised individuals (5)(6)(7)(8).…”
mentioning
confidence: 99%